Deep Ecology - Witoszek, Nina 1954-; Mueller, Martin Lee (2017)
This introductory chapter interrogates the intellectual robustness and mobilizing potential of Arne Naess’s deep ecology in the 21st century. Our contention is that deep ecology is not a spent force, as some influential Western philosophers argue in this volume. On the contrary, ecophilosophy has left a legacy which remains a significant part of the ongoing cultural innovation for a sustainable future. As several essays in this collection show, Arne Naess’ thought feeds into new, science-based visions of the relationship between humans and nature. More importantly, it has got a new lease of life in the South, where biocentric cosmovisions play an ever more important role, not just in philosophical, but political debates which have an impact on Latin America’s future.
Keywords: ecophilosophy -- cultural innovation -- social impact of philosophy -- panpsychism -- the future of deep ecology